1992
DOI: 10.2337/diab.41.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Poly I:C Induces Development of Diabetes Mellitus in BB Rat

Abstract: Polyinosinic polycytidilic acid (poly I:C), an inducer of alpha-interferon, accelerates the development of diabetes in diabetes-prone (DP) BioBreeding (BB) rats. This study investigates the effect of administering poly I:C to a diabetes-resistant (DR) strain of BB rats. We compared the incidence of diabetes, the degree of insulitis, the number of NK cells, helper-inducer cells, cytotoxic-suppressor cells, Ia+ T cells, RT6.1+ T cells, and NK cell bioactivity in DR rats treated with saline and with a 5 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Poly(I:C) was able to prevent diabetes in NOD (non-obese diabetic) mice 38 , but it was shown in diabetes-prone bio-breeding (DP-BB) rats that poly(I:C) can accelerate 39,40 or prevent diabetes, depending on the dosage used 41 . These contradictory observations may be partially explained by differences in doses and different kinetics of poly(I:C).…”
Section: Discussionmentioning
confidence: 99%
“…Poly(I:C) was able to prevent diabetes in NOD (non-obese diabetic) mice 38 , but it was shown in diabetes-prone bio-breeding (DP-BB) rats that poly(I:C) can accelerate 39,40 or prevent diabetes, depending on the dosage used 41 . These contradictory observations may be partially explained by differences in doses and different kinetics of poly(I:C).…”
Section: Discussionmentioning
confidence: 99%
“…dsRNA is an active component of a viral infection that stimulates host antiviral responses, including the production of cytokines and nitric oxide (17)(18)(19)(20). The synthetic dsRNA molecule poly(I-C) also activates the antiviral response (16) and has been shown to stimulate the development of diabetes in diabetesresistant BioBreeding rats and to accelerate disease development in diabetes-prone BioBreeding rats (21,22). We have shown that dsRNA, in combination with IFN-␥, induces islet dysfunction and destruction by a mechanism that is dependent on the expression of iNOS and production of nitric oxide by ␤ cells (23,24).…”
mentioning
confidence: 92%
“…These antiviral responses can be mimicked by the synthetic dsRNA polyinosinic-polycytidylic acid (PIC) (15,16). In vivo, PIC triggers the development of hyperglycemia in diabetes-resistant BioBreeding rats and accelerates the development of the disease in diabetes-prone BioBreeding rats (17,18). In vitro, PIC inhibits glucose-stimulated insulin biosynthesis in mouse islets (19) and, when used in combination with IFN-␥, decreases rat islet cell function and viability (11,20).…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%